2004
DOI: 10.3102/00346543074004473
|View full text |Cite
|
Sign up to set email alerts
|

Improving Intergroup Relations in Higher Education: A Critical Examination of the Influence of Educational Interventions on Racial Bias

Abstract: This study examines the influence of various educational interventions in higher education on students' racial bias. The author reviews studies in four principle domains: multicultural courses, diversity workshops and training, peer-based interventions, and service-based interventions. He pays particular attention to the varied approaches, measures, and research designs used to assess the effectiveness of interventions. He concludes with specific recommendations for improving the quality of intervention studie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

11
147
0
5

Year Published

2008
2008
2020
2020

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 145 publications
(163 citation statements)
references
References 83 publications
11
147
0
5
Order By: Relevance
“…For example, several researchers found that the number of students of color on a campus is linked with students' interactions across race (Chang, 1999;Chang, Astin, & Kim, 2004;Chang, Denson, Sáenz, & Misa, 2006;Pike & Kuh, 2006), and this is particularly true for White students Sáenz, Ngai, & Hurtado, 2007). Thus, the influence of structural diversity can be understood as directly enhancing the opportunity for intergroup contact, which in turn affects educational outcomes over time (Chang, 1999;Chang et al, 2004;Gurin et al, 2002;Engberg, 2004;Jayakumar, 2007;Pike & Kuh, 2006). In other words, the presence of diverse peers works indirectly through students' experiences and interactions with people of different racial and ethnic backgrounds to affect a host of educational outcomes identified later in this review.…”
Section: Structural Diversitymentioning
confidence: 99%
“…For example, several researchers found that the number of students of color on a campus is linked with students' interactions across race (Chang, 1999;Chang, Astin, & Kim, 2004;Chang, Denson, Sáenz, & Misa, 2006;Pike & Kuh, 2006), and this is particularly true for White students Sáenz, Ngai, & Hurtado, 2007). Thus, the influence of structural diversity can be understood as directly enhancing the opportunity for intergroup contact, which in turn affects educational outcomes over time (Chang, 1999;Chang et al, 2004;Gurin et al, 2002;Engberg, 2004;Jayakumar, 2007;Pike & Kuh, 2006). In other words, the presence of diverse peers works indirectly through students' experiences and interactions with people of different racial and ethnic backgrounds to affect a host of educational outcomes identified later in this review.…”
Section: Structural Diversitymentioning
confidence: 99%
“…Aligned with this strategy, many institutions have incorporated diversity courses throughout the undergraduate curriculum as both general education requirements and as part of broader departments with ethnic/cultural emphases (Engberg, 2004;Humphreys, 2000;Nelson Laird, 2003). While there is wide variation across college campuses, diversity courses typically incorporate readings and materials on race, ethnicity, gender, sexual orientation and oppression in conjunction with structured intergroup relations activities (Adams, Bell, & Griffin, 2007;Engberg, 2004;Nelson Laird, 2003).…”
mentioning
confidence: 98%
“…Demonstrating whether a university is below or above the expected benchmark is not a measure of their success in terms of establishing more critical relationships with international students. The analysis therefore needs to encompass the relational nature of student individual characteristics, as well as teaching and other organisational factors to then assess the contribution of the relationship between them to more inclusive intercultural interaction in the classroom (Engberg, 2004). To assess this contribution multiple regression and multiple modelling analyses of student data as well as work done towards greater equivalence of international students could be conducted.…”
Section: So What Could These Metrics Be?mentioning
confidence: 99%